A multi criteria analysis and comparison of primary copper processing options - Lusinga, Dion (Centre for Bioprocess Engineering Research, 2015)
In the present study a methodology and a spreadsheet model were developed with the aim of integrating techno-economic and environmental objectives simultaneously during decision making. The model was developed specifically for the copper industry, mainly due to the wide array of different processing technologies and operational synergies that exist in this industry.